PERTUMBUHAN ROHANI BERDASARKAN 1 PETRUS 2:1-4 DI KOMUNITAS NGOBROLIN PAPI SURGAWI JAKARTA - Hendry, Hendry; Susanta, Vonny A. (STT Kingdom, 2024)
This study examines the impact of some church leaders' and congregation members' indifference towards spiritual growth, which can lead to stagnation in faith development. Challenges in Christian spiritual growth often arises from life’s issues, which can either strengthen or disrupt one's faith. Employing a descriptive qualitative approach, this research involved six church leaders as subjects. Data were collected through semi-structured interviews and validated through rigorous checking. Data analysis followed three main stages: data condensation, data presentation, and conclusion drawing. The findings indicate that both the understanding and application of spiritual growth principles based on 1 Peter 2:1-4 within the Ngobrolin Papi Surgawi Jakarta community are still suboptimal. This research highlights the need for improved understanding and application of spiritual growth principles to prevent stagnation in faith and support ongoing spiritual development.